The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.cllc.2017.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Local Radiotherapy Intensification for Locally Advanced Non–small-cell Lung Cancer – A Call to Arms

Abstract: Chemoradiotherapy, the standard of care for locally advanced non-small-cell lung cancer (NSCLC), often fails to eradicate all known disease. Despite advances in chemotherapeutic regimens, locally advanced NSCLC remains a difficult disease to treat, and locoregional failure remains common. Improved radiographic detection can identify patients at significant risk of locoregional failure after definitive treatment, and newer methods of escalating locoregional treatment may allow for improvements in locoregional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 75 publications
(109 reference statements)
0
10
0
Order By: Relevance
“…Escalating local therapy from conventional radiation using fusion with imaging, including PET-CT to select high-risk patients and using modern techniques (SBRT/lattice), allow for the intensification of treatment. We feel, as do Kalman et al, that a clinical trial incorporating this concept is highly indicated [22].…”
Section: Discussionmentioning
confidence: 99%
“…Escalating local therapy from conventional radiation using fusion with imaging, including PET-CT to select high-risk patients and using modern techniques (SBRT/lattice), allow for the intensification of treatment. We feel, as do Kalman et al, that a clinical trial incorporating this concept is highly indicated [22].…”
Section: Discussionmentioning
confidence: 99%
“…The experience acquired in stage I NSCLC -with excellent results-has aroused the interest of using this treatment in other stages of this illness 32 . In fact, SBRT for NSCLC is a very dynamic field and a call upon the thoracic oncology community is being made encouraging the design and development of new studies 33 .…”
Section: Stereotactic Body Radiation Therapymentioning
confidence: 99%
“…A multi-institutional trial has been proposed that would use a SBRT boost to metabolically active residual disease seen on PET-CT 2-4 weeks after chemoradiation treatment completion (47). Patients with a complete response would be observed.…”
Section: Adapted Therapymentioning
confidence: 99%